2011
DOI: 10.1063/1.3641965
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of fast ions from surface modulated nanostructure targets irradiated by high intensity short-pulse lasers

Abstract: It's shown that the imposition of sub-laser wavelength relief structures on the surface of mass-limited-targets results into several folds higher short-pulse laser absorption, and consequently the efficient generation of fast ions. The optimum relief parameters for enhanced short-pulse laser absorption and higher ion acceleration are estimated numerically by particle-in-cell simulations and then corroborated by analytical scalings. The stability of the pre-imposed surface modulation during the laser pulse foil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 24 publications
(23 reference statements)
2
57
0
Order By: Relevance
“…With the help of the modified code PSC, the modelling was performed for different targets. In 2D simulations with our PIC code [6] It was shown [18] that in case of a target with a non-structured rear side the electric field at the rear side has a regular profile. Contrary, at the structured front side, the field reproduces a relief distribution.…”
Section: Simulation Modelmentioning
confidence: 99%
“…With the help of the modified code PSC, the modelling was performed for different targets. In 2D simulations with our PIC code [6] It was shown [18] that in case of a target with a non-structured rear side the electric field at the rear side has a regular profile. Contrary, at the structured front side, the field reproduces a relief distribution.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Various simulation works attribute the observed improvement to a surface area increase and the local field enhancement introduced by the roughness [22][23][24][25]. Recently, several authors have shown that larger scale structures can give rise to enhanced production of hot electrons and/or high energy ions [26][27][28].…”
Section: B Target Designmentioning
confidence: 99%
“…To increase the number and energy of the hot electrons much effort has been spent on the improvement of the conversion efficiency of laser energy into hot electron energy. To foster conversion efficiency, not only the laser parameters, i.e., laser intensity, pulse duration and energy, but also the target design can be tuned [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%